2017
DOI: 10.1093/europace/euw330
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation vs. radiofrequency ablation for treatment of paroxysmal atrial fibrillation: a systematic review and meta-analysis

Abstract: Compared with RF ablation, cryoablation present a comparable long-term AF/atrial tachycardial-free survival and procedure-related adverse events. Meanwhile, cryoablation markedly shorten the procedure time, nonetheless, with negligible impact on the fluoroscopy time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 37 publications
5
45
1
1
Order By: Relevance
“…In our study, cryoenergy was chosen as the preferred energy source for PVI. According to recent AF ablation guidelines and position papers, 15,16 cryoablation has been proven to be as effective as radiofrequency in PVI and less associated with intraprocedural thrombi. 17 An "extended" AF ablative approach (eg, posterior wall isolation or an isoprenaline challenge for extrapulmonary AF foci ablation), for which radiofrequency may be more effective, has not yet been introduced in the combined procedure protocol, and several recent experiences proved cryoablation PVI to be effective in both patients with persistent AF and those with long-standing persistent AF.…”
Section: Cryoballoon Ablation and Laac Combined Proceduresmentioning
confidence: 99%
“…In our study, cryoenergy was chosen as the preferred energy source for PVI. According to recent AF ablation guidelines and position papers, 15,16 cryoablation has been proven to be as effective as radiofrequency in PVI and less associated with intraprocedural thrombi. 17 An "extended" AF ablative approach (eg, posterior wall isolation or an isoprenaline challenge for extrapulmonary AF foci ablation), for which radiofrequency may be more effective, has not yet been introduced in the combined procedure protocol, and several recent experiences proved cryoablation PVI to be effective in both patients with persistent AF and those with long-standing persistent AF.…”
Section: Cryoballoon Ablation and Laac Combined Proceduresmentioning
confidence: 99%
“… However, recently, a meta‐analysis reported that no differences in the incidence of stroke/TIA were found between RFCA and CB‐A. The reason for the discrepancy between animal experiments and clinical practice is unclear. Rare incidence of stroke/TIA might be an important contributor which might result in an insufficient statistical power to detect differences between RFCA and CB‐A in current trials.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of cryoballoon ablation in paroxysmal AF, including more challenging or specific clinical settings such as elderly patients, patients with heart failure, or patients undergoing first-line ablation, have been confirmed in several other studies [8][9][10]. Cryoablation may have the additional advantage of shorter procedure times [11,12] and appears to be less operator-dependent and more reproducible compared with RF ablation [13]. This is an important aspect because success rates of RF ablation for AF are reported to be operator-dependent [14].…”
Section: Choice Of the Appropriate Techniquementioning
confidence: 91%